Penyelidikan Kekuatan Tekan Dan Laju Keausan Komposit Dengan Filler Palm Slag Sebagai Bahan Penyusun Kanvas Rem Sepeda Motor - Jon Prisno Riduan; Muftil Badri; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Palm slag as waste burning of palm shells and bunches for boiler fuel is available in abundance. Availability of abundant is potential to be developed as a filler of brake composite. The using of palm slag as filler composite non-asbestos brake pads have been studied and potential to be used as a substitute for asbestos brake pads motorcycle. The purpose of this study was to determine the effect of variations in the initial compacting pressure and sintering temperature on the compressive strength and the wear rate of the composite. In this study the manufacture of composite brake using materials with a composition of 40% palm slag, 20% steel powder, 20% phenolic resin, 10% alumina, and 10% graphite. Manufacture of composites using powder metallurgy techniques by varying the compaction pressure at 254, 508, and 762 MPa, and sintering temperatures of 150, 160, and 170oC. Increasing compaction pressure and sintering temperature does not always affect the compressive strength and the wear rate of composite brake. Initial compaction pressure affecting the increase in compressive strength is 508 MPa at 150 and 160oC sintering temperature. Initial compaction pressure affecting decrease the wear rate is 254 and 508 MPa at sintering temperatures of 150 and 160oC.Keywords: palm slag, compacting pressure, sintering temperature, compressive strength, wear rate